Rancang Bangun Smart System Pelayanan Servis Kendaraan Bermotor Berbasis Arduino Mega 2560 - Apriadi, Revan; Putra, Okta Andrica; Naf’an, Emil (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this research is to provide convenience and development in carrying out motorcycle servicing services effectively. In identifying problems with the smart motor vehicle service service system, it was found that the system used was still manual and had not been clearly coordinated. Efforts must be made, for example, to create a technology-based smart service system. such as using Rfid, Keyboard, Buzzer, Push Button, LED, Speaker The application of a smart system for servicing motorized vehicles can be carried out properly and connected to the Arduino Mega 2560. With a smart system for servicing motorized vehicles, this will greatly help the existing service system at the service station. motorbike or repair shop. By using the Arduino Mega 2560 microcontroller, you can properly control the motor vehicle service smart system by utilizing the RFID sensor.